A salt-tolerant CO2 foam flooding system, its preparation method and application method
Patent Information
- Application Number
- CN202610847800.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-12
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-06-12
AI Technical Summary
但在实际地层应用中,地层的矿化度高,会影响泡沫的稳定性,且疏水改性纳米二氧化硅颗粒,疏水性会影响其稳泡性能
1.本申请提供的耐盐型CO2泡沫驱油体系,与CO2交替注入油藏,利用形成的泡沫在在多孔介质中产生的贾敏效应,使后续注入的CO2的波及范围扩大,能够改善CO2驱效果,提高原油采收。
Smart Images

Figure CN122381790B_ABST
Abstract
Description
Technical Field
[0001] This application relates to the field of oil extraction technology, and in particular to a salt-tolerant CO2 foam flooding system, its preparation method, and its application method. Background Technology
[0002] CO2 flooding is a commonly used tertiary oil recovery technology in the mid-to-late stages of oilfield development. CO2 flooding significantly improves oil recovery by reducing crude oil viscosity, increasing formation energy, lowering oil-water interfacial tension, and achieving miscibility with crude oil, making it one of the most promising methods for enhancing oil recovery. However, CO2 flooding suffers from severe gas channeling and viscous fingering phenomena, which negatively impact oil recovery. Studies have shown that foam flooding technology can effectively solve the problems of gas channeling and low sweep efficiency during CO2 flooding.
[0003] In CO2-driven foam-displacement oil recovery systems, foaming agents are crucial, making them a hot research topic in this field. Common foaming agents include sulfonate surfactants and fatty alcohol polyoxyethylene ether surfactants. However, conventional foaming agents have limited bubble-forming properties. Furthermore, foam is a thermodynamically unstable gas-liquid dispersion system, and it easily defoams after foaming, thus limiting the reach and oil displacement performance of CO2.
[0004] Existing technologies primarily improve foam stability by compounding multiple surfactants, developing novel surfactants, or adding foam stabilizers to the foam system. For example, patent CN108570318A discloses a CO2 foaming liquid composition for oilfield use, comprising fatty alcohol polyoxyethylene ether sulfate, α-olefin sulfonate, alkyl glycoside, coconut oil diethanolamide, hydrophobically modified nano-silica particles, and water. This CO2 foaming liquid composition can form rich and stable foam. However, in practical formation applications, high formation salinity can affect foam stability, and the hydrophobicity of the hydrophobically modified nano-silica particles can negatively impact their foam-stabilizing properties.
[0005] Therefore, it is still necessary to provide a novel salt-resistant CO2 foam flooding system. Summary of the Invention
[0006] The purpose of this invention is to overcome the defects and shortcomings of the existing technology and provide a salt-resistant CO2 foam flooding system, its preparation method and application method. This system still has good stability under high salt conditions and can effectively improve the CO2 flooding effect and increase the recovery rate.
[0007] To achieve the above objectives, the technical solution adopted in this application is as follows: According to one aspect of this application, a salt-resistant CO2 foam flooding system is provided, comprising, by mass percentage: 0.1-0.3% nonionic surfactant, 0.05-0.1% alkylbenzene sulfonate, 0.1-0.3% modified nano-shell powder, and the balance being water; wherein, The nonionic surfactant comprises fatty alcohol polyoxyethylene ether and PEG-n glyceryl isostearate; The modified nano-shell powder is prepared by first pretreating the nano-shell powder with an aminosilane coupling agent, and then using polybasic acid anhydrides and polyols to polymerize in situ on the surface of the nano-shell powder.
[0008] This application combines two nonionic surfactants with anionic surfactants and adds a certain amount of modified nano-shell powder to prepare a CO2 foam flooding system. The components in this system work synergistically to produce excellent foaming and stabilizing capabilities. By utilizing the Jamin effect generated by the foam in the porous medium, the sweep range of the subsequently injected CO2 is expanded, which can improve the CO2 flooding effect and enhance crude oil recovery. Furthermore, this system still has good stability under high temperature and high salinity conditions and can adapt to more complex reservoirs.
[0009] Further, the mass ratio of fatty alcohol polyoxyethylene ether to PEG-n glycerol isostearate in the nonionic surfactant is 10:(2-3.5), for example, the mass ratio can be 10:2, 10:2.1, 10:2.2, 10:2.3, 10:2.4, 10:2.5, 10:2.6, 10:2.7, 10:2.8, 10:2.9, 10:3, 10:3.1, 10:3.2, 10:3.3, 10:3.4, 10:3.5 or any range therebetween.
[0010] Furthermore, the fatty alcohol polyoxyethylene ether has the structural formula shown in formula (I): RO-[CH2-CH2-O] m -H type (I); In formula (I), 9 ≤ m ≤ 16, and R is a C12 to C18 alkyl group; For example, the fatty alcohol polyoxyethylene ether is dodecyl alcohol polyoxyethylene ether (9), tetradecyl alcohol polyoxyethylene ether (9), hexadecyl alcohol polyoxyethylene ether (9), octadecyl alcohol polyoxyethylene ether (9), dodecyl alcohol polyoxyethylene ether (10), tetradecyl alcohol polyoxyethylene ether (10), hexadecyl alcohol polyoxyethylene ether (10), octadecyl alcohol polyoxyethylene ether (10), dodecyl alcohol polyoxyethylene ether (16), tetradecyl alcohol polyoxyethylene ether (16), hexadecyl alcohol polyoxyethylene ether (16), octadecyl alcohol polyoxyethylene ether (16), etc., or it can be dodecyl / tetradecyl alcohol polyoxyethylene ether (9), tetradecyl / hexadecyl alcohol polyoxyethylene ether (9), hexadecyl / octadecyl alcohol polyoxyethylene ether (9), etc., the "(9)" in the chemical name is m in the above structural formula (I), and " / " indicates mixed carbon, for example, "dodecyl / tetradecyl" indicates a mixture of C12 fatty alcohol and C14 fatty alcohol.
[0011] Further, in the PEG-n glycerol isostearate, n refers to the degree of polymerization, which is an integer from 15 to 20. That is, PEG-n glycerol isostearate is selected from any one or a combination of several of PEG-15 glycerol isostearate, PEG-16 glycerol isostearate, PEG-17 glycerol isostearate, PEG-18 glycerol isostearate, PEG-19 glycerol isostearate, and PEG-20 glycerol isostearate. PEG-n glycerol isostearate is commercially available or prepared using methods well-known to those skilled in the art.
[0012] Furthermore, the alkylbenzene sulfonate is selected from C18 to C30 alkylbenzene sulfonates, such as octadecylbenzene sulfonate, eicosylbenzene sulfonate, triacontylbenzene sulfonate, etc.; the salt is any one or a combination of sodium salt, potassium salt, and ammonium salt.
[0013] This application selects the above-mentioned surfactants for compounding. Among them, fatty alcohol polyoxyethylene ether has strong emulsifying ability, PEG-n glycerol isostearate has good temperature resistance, and alkylbenzene sulfonate has strong viscosity-reducing / interfacial tension-reducing ability and good compatibility with crude oil at its lipophilic end. The three surfactants are compounded in a specific ratio, which has good foaming and foam-stabilizing properties. It can effectively reduce the gas mobility ratio to the water-oil mobility ratio, avoid gas channeling and viscous fingering phenomena in CO2 foam oil displacement, and achieve a 1+1+1>3 effect. The salt resistance of this system is also improved to a certain extent, and it still has good foaming and foam-stabilizing ability under high salinity conditions. However, it should be noted that the three surfactants need to be kept within a specific ratio to ensure that the emulsification, viscosity reduction, high temperature resistance, and salt resistance effects are maximized and the salt resistance is improved.
[0014] Furthermore, in the preparation process of the modified nano-shell powder, the particle size of the nano-shell powder is 20-80 nm; the nano-shell powder is prepared by the following method: soaking shells in hydrochloric acid solution for 12-16 h, washing with water, drying, pulverizing to make shell powder, and calcining under anaerobic conditions for 4-5 h at a calcination temperature of 900-1000 °C; then ball milling and sieving to obtain nano-shell powder; the mass fraction of hydrochloric acid solution is 1%.
[0015] Furthermore, in the preparation process of the modified nano-shell powder, the pretreatment step using an aminosilane coupling agent is as follows: Nano-shell powder was mixed with anhydrous ethanol at a solid-liquid ratio of 1g:(30-50)mL to obtain a nano-shell powder dispersion. An aminosilane coupling agent was added, and the mixture was reacted at 70-75℃ for 4-6 hours. After the reaction, the mixture was washed with water and dried to obtain pretreated nano-shell powder. The amount of aminosilane coupling agent was 3-7% of the mass of the nano-shell powder. The aminosilane coupling agent was selected from any one or a combination of several of γ-aminopropyltriethoxysilane (KH-550), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH-602), and N-(β-aminoethyl)-γ-aminopropyltriethoxysilane (KH-792).
[0016] Furthermore, in the preparation process of modified nano-shell powder, the in-situ polymerization steps of polyacid anhydrides and polyols on the surface of nano-shell powder are as follows: Pretreated nano-shell powder, polyacid anhydride, and polyol were mixed in a mass ratio of 10:(5-8):(4-7). 0.05-0.2% of the total mass of the raw materials was added to the mixture. Nitrogen gas was introduced and the temperature was slowly raised to 140-160℃ for 6-12 hours. The mixture was then cooled to room temperature, repeatedly washed with ethanol, and dried to obtain modified nano-shell powder. The polyacid anhydride is selected from succinic anhydride and hydrogenated trimellitic anhydride in a molar ratio of 1:(0.3-0.5); isosorbide and tris(2-hydroxyethyl) isocyanurate; The polyol is selected from isosorbide and tris(2-hydroxyethyl) isocyanurate in a molar ratio of 1:(0.2-0.3); The mass ratio of the nano-shell powder, polyacid anhydride, and polyol is 10:(4-7):(2-4). The catalyst is selected from p-toluenesulfonic acid, dodecylbenzenesulfonic acid, organotin catalysts, etc., such as stannous octoate and / or dibutyltin dilaurate.
[0017] The aforementioned nano-shell powder consists of nano-sized particles that exhibit good foam stability at high temperatures. However, the nano-shell powder has a large number of hydroxyl groups on its surface, resulting in strong hydrophilicity, poor dispersibility, and a tendency to agglomerate. This application addresses this issue by first introducing an aminosilane coupling agent onto the surface of the nano-shell powder, thereby reducing the surface hydroxyl content and increasing hydrophobicity, which is beneficial for reducing oil-water interfacial tension. Then, through in-situ polymerization, ester polymers are formed on the surface of the nano-shell powder, further enhancing its hydrophobicity and contributing to further reducing oil-water interfacial tension and improving crude oil recovery. In addition, the introduction of polyester also helps improve salt resistance, enabling it to maintain good oil displacement performance even at high salinity levels.
[0018] Furthermore, the water in the salt-tolerant CO2 foam flooding system is any one of formation water, tap water, or mineralized water.
[0019] Optionally, when mineralized water is selected as the water in the salt-tolerant CO2 foam flooding system, the salinity of the mineralized water is 10,000 to 200,000 mg / L.
[0020] In a further embodiment, the salt-resistant CO2 foam flooding system also contains sodium polyglutamate and / or propyl gallate as additives, wherein the mass content of sodium polyglutamate in the salt-resistant CO2 foam flooding system is 0-0.03%, and the mass content of propyl gallate in the salt-resistant CO2 foam flooding system is 0-0.02%.
[0021] Studies have found that adding a certain amount of sodium polyglutamate and / or propyl gallate to a salt-tolerant CO2 foam flooding system helps to further improve the foaming and foam stabilization performance at high salinity. In particular, when sodium polyglutamate is added simultaneously, its half-life at high salinity can be increased by more than 410% compared with conventional foam, and the recovery rate can be increased by more than 38%.
[0022] According to another aspect of this application, a method for preparing a salt-resistant CO2 foam flooding system is provided, comprising the following steps: The nonionic surfactant and alkylbenzene sulfonate were dissolved in water, and then modified nano-shell powder was added and mixed evenly to obtain the salt-resistant CO2 foam oil displacement system.
[0023] Furthermore, when sodium polyglutamate is added to the salt-resistant CO2 foam flooding system, the preparation method further includes the following steps: dissolving sodium polyglutamate in solution B, and then adding modified nano-shell powder.
[0024] Furthermore, when propyl gallate is added to the salt-resistant CO2 foam flooding system, the preparation method further includes the following steps: dissolving propyl gallate in hot water at 50°C, restoring it to room temperature, adding it to solution B and mixing well, and then adding modified nano-shell powder.
[0025] Furthermore, when sodium polyglutamate and propyl gallate are added to the salt-resistant CO2 foam flooding system, the preparation method further includes the following steps: dissolving sodium polyglutamate in solution B, dissolving propyl gallate in hot water at 50°C, then restoring it to room temperature and adding it to solution B for mixing, and then adding modified nano-shell powder.
[0026] According to another aspect of this application, a method for applying the salt-resistant CO2 foam flooding system described above is provided, the method comprising first injecting the salt-resistant CO2 foam flooding system and then injecting a CO2 slug.
[0027] Compared with the prior art, this application has the following beneficial effects: 1. The salt-tolerant CO2 foam flooding system provided in this application is injected into the reservoir alternately with CO2. By utilizing the Jamin effect generated by the foam in the porous medium, the sweep range of the subsequently injected CO2 is expanded, which can improve the CO2 flooding effect and increase crude oil recovery.
[0028] 2. This application selects two nonionic surfactants, fatty alcohol polyoxyethylene ether and PEG-n glycerol isostearate, and an alkylbenzene sulfonate anionic surfactant for compounding. It has good foaming properties, can effectively reduce the gas flow rate to water-oil flow rate, avoid gas channeling and viscous fingering phenomena in CO2 foam oil displacement process, and has good salt resistance.
[0029] 3. The salt-tolerant CO2 foam flooding system of this application incorporates modified nano-shell powder as a foam stabilizer, which can ensure good foaming and foam stabilizing ability even under a salinity of 200,000 mg / L, thereby helping to improve crude oil recovery. Attached Figure Description
[0030] Figure 1 The images show the infrared spectra of the modified and unmodified nano-shell powders in Example 1 of this application. Detailed Implementation
[0031] To more clearly illustrate the overall concept of this application, a detailed description is provided below with reference to embodiments. Numerous specific details are set forth in the following description to provide a more thorough understanding of the invention. However, it will be apparent to those skilled in the art that the invention can be practiced without one or more of these details. In other instances, certain technical features well-known in the art have not been described to avoid confusion with the invention.
[0032] Before further describing specific embodiments of the present invention, it should be understood that the scope of protection of the present invention is not limited to the specific embodiments described below; it should also be understood that the terminology used in the embodiments of the present invention is for describing specific embodiments and not for limiting the scope of protection of the present invention. Test methods in the following embodiments that do not specify specific conditions are generally performed under conventional conditions or according to the conditions recommended by the respective manufacturers. Preparation methods that do not specify specific methods are generally prepared using equipment or conventional methods well known in the art.
[0033] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the exemplary embodiments according to this application. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0034] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise stated in the present invention, both endpoints of each numerical range and any value between the two endpoints may be selected. Unless otherwise defined, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art. In addition to the specific methods, apparatus, and materials used in the embodiments, based on the knowledge of the prior art possessed by one of ordinary skill in the art and the description of this invention, any prior art methods, apparatus, and materials similar to or equivalent to those described, apparatus, and materials in the embodiments of this invention may be used to implement the present invention.
[0035] Unless otherwise specified, in the following embodiments, reagents or instruments whose manufacturers are not indicated are all conventional products that can be purchased commercially.
[0036] Unless otherwise stated, the experimental methods, detection methods, and preparation methods disclosed in this invention all employ conventional techniques in the fields of microbiology, biochemistry, analytical chemistry, cell culture, and related areas.
[0037] The present application will be further described below by way of specific embodiments.
[0038] Example 1 This embodiment provides a salt-resistant CO2 foam flooding system, comprising the following components by mass percentage: 0.1% nonionic surfactant, 0.1% sodium octadecylbenzenesulfonate, 0.1% modified nano-shell powder, with the balance being tap water; wherein, The nonionic surfactant contains dodecyl alcohol polyoxyethylene ether (16) and PEG-15 glyceryl isostearate in a mass ratio of 10:2; Modified nano-shell powder was prepared by the following method: Shells were soaked in a 1% hydrochloric acid solution for 12 hours, washed, dried, and pulverized to obtain shell powder. The powder was then calcined for 5 hours under anaerobic conditions at a temperature of 900℃, followed by ball milling and sieving to obtain nano-shell powder with an average particle size of 20 nm. The nano-shell powder was mixed with anhydrous ethanol at a solid-liquid ratio of 1 g:30 mL to obtain a nano-shell powder dispersion. 3% (by weight) of KH-602 (by mass of the nano-shell powder) was added, and the mixture was reacted at 70℃ for 4 hours. After the reaction was completed, water was added... Wash and dry to obtain pretreated nano-shell powder; mix the pretreated nano-shell powder, polyacid anhydride (succinic anhydride and hydrogenated trimellitic anhydride in a molar ratio of 1:0.3), and polyol (isosorbide and tris(2-hydroxyethyl) isocyanurate in a molar ratio of 1:0.2) at a mass ratio of 10:5:4, add 0.05% p-toluenesulfonic acid of the total raw material mass, purge with nitrogen and slowly heat to 140℃ for 6 hours, cool to room temperature, wash repeatedly with ethanol, and dry to obtain modified nano-shell powder. The infrared spectra of unmodified and modified nano-shell powder are shown below. Figure 1 As shown, compared to unmodified nano-shell powder, modified nano-shell powder exhibits higher performance at 1060 cm⁻¹. -1 The area near the peak is a characteristic peak of the Si-O-Si bond, at 1740 cm⁻¹. -1 The nearby peak is the stretching vibration peak of the C=O bond, at 1570 cm⁻¹. -1 Nearby amide NH bending This embodiment also provides a method for preparing the above-mentioned salt-resistant CO2 foam flooding system, including the following steps: dissolving nonionic surfactant and sodium octadecylbenzenesulfonate in tap water, and then adding modified nano-shell powder and mixing evenly to obtain the salt-resistant CO2 foam flooding system.
[0039] Example 2 This embodiment provides a salt-resistant CO2 foam flooding system, comprising the following components by mass percentage: 0.3% nonionic surfactant, 0.05% sodium octadecylbenzenesulfonate, 0.3% modified nano-shell powder, and the balance being tap water; wherein, The nonionic surfactant comprises octadecyl alcohol polyoxyethylene ether (9) and PEG-20 glyceryl isostearate in a mass ratio of 10:3.5; Modified nano-shell powder was prepared by the following method: Shells were soaked in a 1% hydrochloric acid solution for 16 hours, washed, dried, and pulverized to obtain shell powder. The powder was then calcined for 4 hours under anaerobic conditions at a temperature of 1000℃, followed by ball milling and sieving to obtain nano-shell powder with an average particle size of 80 nm. The nano-shell powder was mixed with anhydrous ethanol at a solid-liquid ratio of 1 g:50 mL to obtain a nano-shell powder dispersion. 7% (by weight) of KH-550 (based on the mass of the nano-shell powder) was added, and the mixture was reacted at 75℃ for 6 hours. After the reaction was completed, water was added... Wash and dry to obtain pretreated nano-shell powder; mix the pretreated nano-shell powder, polyacid anhydride (succinic anhydride and hydrogenated trimellitic anhydride in a molar ratio of 1:0.5), and polyol (isosorbide and tris(2-hydroxyethyl) isocyanurate in a molar ratio of 1:0.3) in a mass ratio of 10:8:7, add 0.05% of p-toluenesulfonic acid of the total mass of the raw materials and mix, purge with nitrogen and slowly heat to 140℃ for 6h, cool to room temperature, wash repeatedly with ethanol, and dry to obtain modified nano-shell powder.
[0040] This embodiment also provides a method for preparing the above-mentioned salt-resistant CO2 foam flooding system, including the following steps: dissolving nonionic surfactant and sodium octadecylbenzenesulfonate in tap water, and then adding modified nano-shell powder and mixing evenly to obtain the salt-resistant CO2 foam flooding system.
[0041] Example 3 The difference from Example 2 is that PEG-15 glyceryl isostearate is replaced with PEG-12 glyceryl isostearate.
[0042] Example 4 The difference from Example 2 is that in the preparation of modified nano-shell powder, the polyacid anhydride is only succinic anhydride.
[0043] Example 5 The difference from Example 2 is that in the preparation of modified nano-shell powder, the polyol is only isosorbide.
[0044] Example 6 The difference from Example 2 is that 0.03% sodium polyglutamate is added to the salt-resistant CO2 foam flooding system.
[0045] Example 7 The difference from Example 2 is that 0.02% of propyl gallate is added to the salt-tolerant CO2 foam flooding system.
[0046] Example 8 The difference from Example 2 is that 0.03% sodium polyglutamate and 0.02% propyl gallate are added to the salt-resistant CO2 foam flooding system.
[0047] Comparative Example 1 The difference from Example 2 is that the nonionic surfactant contains dodecyl alcohol polyoxyethylene ether (16) and PEG-15 glyceryl isostearate in a mass ratio of 10:4.
[0048] Comparative Example 2 The difference from Example 2 is that the nonionic surfactant is only dodecyl alcohol polyoxyethylene ether (16).
[0049] Comparative Example 3 The difference from Example 2 is that the modified nano-shell powder is replaced with pretreated nano-shell powder, and the preparation method of the pretreated nano-shell powder is the same as that in Example 1.
[0050] Comparative Example 4 The difference from Example 2 is that the modified nano-shell powder is replaced with untreated nano-shell powder.
[0051] Experimental Example 1 The Waring-Blender method was used to foam 100 mL of salt-resistant CO2 foam flooding system at 2000 rpm for 5 min. A conventional foam system (0.2% sodium dodecylbenzenesulfonate + 0.2% lauric acid diethanolamide) was used as a comparison. The foaming volume and liquid half-life after aging at room temperature and 130℃ for 72 h are shown in Table 1 below.
[0052] Table 1. Foaming properties
[0053] As shown in the table, the salt-resistant CO2 foam flooding system provided in this application exhibits high foam volume and half-life at room temperature, excellent foaming and stabilizing performance, and good foaming and stabilizing performance even at 130℃, demonstrating good high-temperature stability and applicability to reservoir development at 130℃ or even higher. Compared to Example 2, Comparative Example 1, with its excessive PEG-15 glycerol isostearate in the nonionic surfactant, while exhibiting good high-temperature stability, showed a decrease in overall foam volume and half-life. Comparative Example 2, using only one nonionic surfactant, resulted in a flooding system with high foam volume and half-life at room temperature, but poor high-temperature stability. This indicates that the combined use of two nonionic surfactants helps improve the foaming and stabilizing performance and high-temperature stability of the flooding system. Comparative Example 4, with the use of silane coupling agent-modified nano-shell powder and unmodified nano-shell powder, showed a decrease in foam volume and half-life, which may be due to the agglomeration of the untreated nano-shell powder.
[0054] Experimental Example 2 In the laboratory, simulated formation water with a salinity of 10,000 mg / L and 200,000 mg / L was prepared using analytical grade NaCl and distilled water, respectively. The tap water in the salt-tolerant CO2 foam flooding system was replaced with the simulated formation water. The foaming volume and liquid half-life were tested using the stirring method (Waring-Blender method), and the test method was the same as in Experiment 1. This was used to evaluate the salt tolerance performance, and the results are shown in Table 2 below.
[0055] Table 2. Salt Tolerance
[0056] As shown in the table, compared with conventional foam systems, the salt-resistant CO2 foam flooding system of this application exhibits higher foam volume and half-life under salinity conditions of 10,000 mg / L and 200,000 mg / L. This indicates that the salt-resistant CO2 foam flooding system of this application has good stability under high salinity conditions and can be applied to the development of reservoirs with salinity of 10,000-200,000 mg / L or even higher. Compared with Example 2, the nonionic surfactant composition in Comparative Examples 1 and 2 was changed, resulting in a significant decrease in the foam volume and half-life of the resulting flooding systems. This indicates that the specific ratio of nonionic surfactants to alkylbenzene sulfonates in this application improves the salt resistance of the system. Comparative Example 3 used nano-shell powder treated with a silane coupling agent, and Comparative Example 4 used untreated nano-shell powder. The foam volume and half-life of the systems in Comparative Example 3 were significantly lower than those in Example 2. This indicates that nano-shell powder or nano-shell powder pretreated with a silane coupling agent cannot effectively improve the salt resistance of the system, and further treatment and modification of the nano-shell powder are needed.
[0057] Experimental Example 3 The oil displacement capability of foam was evaluated using a sand-filled pipe model with a length of 400 mm and an inner diameter of 25 mm. The specific experimental procedure is as follows: saturated crude oil was aged at 50℃ for 24 h, and water-driven until the water cut reached 98%. The recovery rate of the first water-driven operation was calculated. A salt-resistant CO2 foam flooding system and a CO2 slug were injected at a flow rate of 0.5 mL / min. Water-driven operation was then continued until the water cut of the produced fluid reached 98%. The final recovery rate and the degree of recovery rate improvement were calculated. The results are shown in Table 3 below.
[0058] Table 3. Oil Displacement Effect
[0059] As shown in the table, the salt-tolerant CO2 foam flooding system provided in this application has a strong oil displacement effect, and can improve the oil recovery rate by more than 30%, with a maximum of more than 38%.
[0060] The above description of the embodiments is provided to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, this application is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of this application without departing from the scope of this application should be within the protection scope of this application.
Claims
1. A salt-tolerant CO2 foam flooding system, characterized in that, By mass percentage, it includes the following components: 0.1–0.3% nonionic surfactant, 0.05–0.1% alkylbenzene sulfonate, and modified nano-shell powder. 0.1%–0.3%, with the remainder being water; among which, The nonionic surfactant comprises fatty alcohol polyoxyethylene ether and PEG-n glycerol isostearate in a mass ratio of 10:(2-3.5), where n is an integer from 15 to 20; The modified nano-shell powder is prepared by first pretreating the nano-shell powder with an aminosilane coupling agent, and then using polyacid anhydrides and polyols to polymerize in situ on the surface of the nano-shell powder. Pretreated nano-shell powder, polyacid anhydride, and polyol are mixed in a mass ratio of 10:(5-8):(4-7). The polyacid anhydride is selected from succinic anhydride and hydrogenated trimellitic anhydride in a molar ratio of 1:(0.3-0.5); the polyol is selected from isosorbide and tris(2-hydroxyethyl) isocyanurate in a molar ratio of 1:(0.2-0.3). The nano-shell powder was prepared by the following method: the shells were soaked in hydrochloric acid solution for 12-16 hours, washed with water, dried, and crushed to make shell powder, and then calcined under anaerobic conditions for 4-5 hours at a temperature of 900-1000°C; then ball-milled and sieved to obtain nano-shell powder; the mass fraction of the hydrochloric acid solution was 1%.
2. The salt-tolerant CO2 foam flooding system according to claim 1, characterized in that, The fatty alcohol polyoxyethylene ether has the following structural formula (I): R-O-[CH2-CH2-O] m -H Formula (I); In formula (I), 9 ≤ m ≤ 20, and R is a C12 to C18 alkyl group.
3. The salt-tolerant CO2 foam flooding system according to claim 1, characterized in that, The alkylbenzene sulfonate is selected from C18 to C30 alkylbenzene sulfonates.
4. The salt-tolerant CO2 foam flooding system according to claim 1, characterized in that, In the preparation process of the modified nano-shell powder, the silane coupling agent pretreatment step is as follows: the nano-shell powder is dispersed in anhydrous ethanol, an aminosilane coupling agent is added, and the reaction is carried out at 70-75°C for 4-6 hours. After the reaction is completed, the nano-shell powder is washed with water and dried to obtain the pretreated nano-shell powder.
5. The salt-resistant CO2 foam flooding system according to claim 1, characterized in that, The in-situ polymerization steps of polyacid anhydrides and polyols on the surface of nano-shell powder are as follows: pretreated nano-shell powder, polyacid anhydrides and polyols are mixed, a catalyst is added, nitrogen gas is introduced, the temperature is raised to 140-160℃ and reacted for 6-12 hours, cooled to room temperature, repeatedly washed with ethanol, and dried to obtain modified nano-shell powder.
6. The salt-tolerant CO2 foam flooding system according to claim 1, characterized in that, The water in the salt-tolerant CO2 foam flooding system can be any one of formation water, tap water, or mineralized water; when mineralized water is selected for the salt-tolerant CO2 foam flooding system, the salinity of the mineralized water is 8000-200000 mg / L.
7. The preparation method of the salt-tolerant CO2 foam flooding system according to any one of claims 1-6, characterized in that, Includes the following steps: The salt-resistant CO2 foam oil displacement system is obtained by uniformly mixing nonionic surfactant, alkylbenzene sulfonate, modified nano-shell powder with water.
8. The application method of the salt-resistant CO2 foam flooding system according to any one of claims 1-7, characterized in that, This includes first injecting a salt-resistant CO2 foam flooding system, and then injecting a CO2 slug.
Citation Information
Patent Citations
CO2 foam foaming liquid composition for oil fields and preparation method thereof
CN108570318A
Nano shell powder foam stabilizer and preparation method thereof
CN119371951A
CO2 oil displacement foam composition and application thereof
CN121736727A